436 - Scaling up a community-based intervention for people affected by dementia: what is the value?. (October 2021) - Stephens, Nathan
Abstract : The Meeting Centres Support Programme [MCSP] provides community-based social, emotional and practical support for people affected by dementia to adjust to the changes dementia brings. Since development in the Netherlands the MCSP has been successfully adapted and implemented in the UK led by the Association for Dementia Studies, University of Worcester. In January (2020), Worcestershire County Council announced £540, 000 to scale up the provision of MCSPs across the county: Worcestershire Meeting Centres Community Support Programme [WMCCSP]. The novel county-wide approach will build real capacity, increasing the amount of people accessing post-diagnostic support, integrating services, reducing inequalities, and improving health and wellbeing; fundamental to the COVD-19 recovery plan (Department of Health and Social Care, 2020). This raises questions about the type of 'value' interventions such as the WCCMCSP should seek to achieve, including how it is captured and measured (Redding, 2016). This becomes more relevant when recognising only a portion of outcomes will be related to health, but much of it is likely to support individual and community wellbeing and development. In this context, understanding and measuring the 'value' is timely. A Concept Analysis (Rogers, 2000) of value in the context of community-based interventions for people affected by dementia informed a robust and systematic definition to assess the value created and/or destroyed by the WMCCSP. The research will develop definitions of value in this area from the perspective of key stakeholders including people affected by dementia. Social Return on Investment principles will be employed to understand outcomes created and/or destroyed by the WMCCSP for stakeholders and measure them within an endogenous framework that encapsulates what is, per say, valuable. Progress on the process, challenges, and breakthroughs of this innovative and developmental approach will be presented at the conference.